Enhanced long-term stability of perovskite solar cells by passivating grain boundary with polydimethylsiloxane (PDMS). Issue 36 (30th August 2019) - Kim, Woochul; Park, Jong Bae; Kim, Hyeonghun; Kim, Kihyeun; Park, Jiyoon; Cho, Sungjun; Lee, Heon; Pak, Yusin; Jung, Gun Young
Abstract : Highly stable perovskite solar cells are achieved by passivating the grain boundaries with PDMS to inhibit the water–perovskite reaction and reduce the trap density, ensuring complete photovoltaic operation even after 5000 h under RH 70%. Abstract : Organic–inorganic hybrid perovskite solar cells (PSCs) have attracted considerable attention due to their superior power conversion efficiency (PCE), which has recently exceeded 22%. However, some issues remain regarding their use in real-life environments, with the most pressing matter being their long-term stability under humid conditions. Hybrid perovskites are naturally vulnerable to water molecules, which can induce the decomposition of perovskite photoactive chemicals such as MAPbI3 and FAPbI3 . Therefore, to achieve commercial-level long-term PSC stability, the adsorption and infiltration of water into the perovskite films must be minimized. Herein, it is demonstrated that polydimethylsiloxane (PDMS) introduced simultaneously during perovskite spin-coating is highly beneficial to passivate the perovskite grains and adjacent grain boundaries (GBs). This not only promotes the formation of lead oxide (PbO) bonds that prevent a water–perovskite reaction, but also contributes to reducing the Pb defect density related to trap-assisted recombination. The photovoltaic performance of the prepared PDMS-passivated PSC is notably enhanced compared to a reference PSC (without PDMS), and surprisingly, more than 90% of the initial PCE (∼15%) is sustained after laboratory storage for 5000 h under 70% relative humidity. These results will pave the way for developing commercial perovskite optoelectronic devices.